2021
DOI: 10.1038/s41598-021-91837-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed endophytic bacterium induces robust plant defense responses against important pathogens

Abstract: Stress caused by pathogens strongly damages plants. Developing products to control plant disease is an important challenge in sustainable agriculture. In this study, a heat-killed endophytic bacterium (HKEB), Bacillus aryabhattai, is used to induce plant defense against fungal and bacterial pathogens, and the main defense pathways used by the HKEB to activate plant defense are revealed. The HKEB induced high protection against different pathogens through the salicylic and jasmonic acid pathways. We report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Heat-killed endophytic strain B. aryabhattai (HKEB) induced defense-related genes protein (PR1) and phytoalexin-deficient 3 in A. thaliana . PR1 gene expression was found to be 20-fold higher in treated plants than control, and other genes found in the study were associated with jasmonic and salicylic acid pathways (Portieles et al, 2021 ). Endophytes exhibit different gene upregulation and a distinct signaling pathway in response to distinct colonization strategies (Morelli et al, 2020 ).…”
Section: Role Of Biofertilizers In Biotic Stress Managementmentioning
confidence: 85%
See 1 more Smart Citation
“…Heat-killed endophytic strain B. aryabhattai (HKEB) induced defense-related genes protein (PR1) and phytoalexin-deficient 3 in A. thaliana . PR1 gene expression was found to be 20-fold higher in treated plants than control, and other genes found in the study were associated with jasmonic and salicylic acid pathways (Portieles et al, 2021 ). Endophytes exhibit different gene upregulation and a distinct signaling pathway in response to distinct colonization strategies (Morelli et al, 2020 ).…”
Section: Role Of Biofertilizers In Biotic Stress Managementmentioning
confidence: 85%
“…In a study by Samain et al ( 2019 ), Paenibacillus strain (PB2) used to control Mycosphaerella graminicola induced pathogenesis-related proteins (PR1) which is considered as marker of SAR. Application of Bacillus aryabhattai activated a durable defense response against pathogens facilitated through salicylic acid/ethylene pathways (Portieles et al, 2021 ). Trichoderma harzianum helps to improve plant immediate resistance against Nezara viridula feeding invasion via enhancing JA marker gene transcript levels (Alınç et al, 2021 ).…”
Section: Role Of Biofertilizers In Biotic Stress Managementmentioning
confidence: 99%
“…The bacterium Bacillus aryabhattai was previously isolated and identified from the wild plant species Glyceria chinensis (Keng) according to Portieles et al [ 26 ]. Samples were collected from the wild plant species G .…”
Section: Methodsmentioning
confidence: 99%
“…The bacterium Bacillus aryabhattai was previously isolated and identified from the wild plant species Glyceria chinensis (Keng) according to Portieles et al [26]. Samples were collected from the wild plant species G. chinensis (Keng) along the Fu Tuan River (35˚20 0 17 00 N, 1192 6 0 8 00 E) within 5 km of the coastal region of Rizhao city in Shandong Province, People's Republic of China.…”
Section: Endophytic Bacterium Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Previous studies have shown that some endophytic bacteria activate plant defense reactions against biotrophic and necrotrophic plant pathogens. In some pathosystems, induction of defense reactions was mediated by the upregulation of PR genes ( Asghari et al, 2020 ; Portieles et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%